PENINGKATAN KINERJA GURU MELALUI SUPERVISI MODEL COACHING DENGAN ALUR TIRTA DI SDN BRINGIN 02 KOTA SEMARANG: Supervisi Model Coaching Alur Tirta - Musri’an; Marno Nugroho; Evi Chamalah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study (1) to determine the planning of improving teacher performance through coaching model supervision with the TIRTA flow. (2) to determine the implementation of improving teacher performance through coaching model supervision with the TIRTA flow. (3) to determine the evaluation of improving teacher performance through coaching model supervision with the TIRTA Flow at SDN Bringin 02 Semarang City. This study uses a qualitative approach. This type of research is a case study. The qualitative research design goes through three stages, namely: orientation, exploration focus, and data analysis. Data collection techniques are interviews, observations and documentation. This study uses source triangulation. Data analysis with three steps: data reduction, data presentation, and drawing conclusions. Research results (1) planning is done by forming a team responsible for improving teacher performance. Then the principal determines the teacher performance improvement program based on the results of the teacher performance evaluation and conducts program socialization. (2) Implementation is done by providing direction and motivation to all teachers. In the implementation, the principal carries out three activities, namely pre-observation, observation and post-observation which show that teachers are more reflective, collaboration between teachers increases. There is an increase in enthusiasm in participating in self-development. Teachers are more open and no longer awkward in conveying shortcomings. Teachers feel an increase in pedagogical skills, becoming more creative and innovative. (3) Evaluation is carried out by conveying the evaluation results openly, providing appreciation. The principal uses the evaluation results to prepare the next coaching program. The principal facilitates sharing sessions, gives awards or recognition to teachers. The conclusion of improving teacher performance through coaching model supervision with the TIRTA flow is good by going through three steps of activity, namely planning, implementation and evaluation